PROFIL LULUSAN PROGRAM STUDI ADMINISTRASI BISNIS TERAPAN TAHUN 2015 DAN RELEVANSINYA DENGAN PENYERAPAN DUNIA KERJA - Rahmat Hidayat; muhammad zainuddin (JURNAL AKUNTANSI, EKONOMI dan MANAJEMEN BISNIS, 2017)
2015 Applied Business Administration Study Program Graaaduates and The Relevance with the Working World. This type of research is descriptive. The population of this research is all of the 2015 Applied Business Administration Study Program Graduate, with the amount of 67 person which all respondents of the research. The absorption number of 2015 Applied Business Administration Study Program Graduate is 0,88 with numbers the difference 0,12 approaching the ideal value which is 1 (one). the relationship between the university courses and the working world show all of the courses that been chosen but there are 17 courses that been selected over than 50% by the graduates. There is a Relevance of Applied Business Administration Study Program Graduate with the absorption of the workforce shown by the percentage of 88,06% are in the relevant category and 11,94% are in the not relevant category.